The spectral characteristics of biochar-derived dissolved organic matter at different pyrolysis temperatures. Issue 5 (October 2021) - He, Changjun; He, Xuwen; Li, Jiajia; Luo, Yong; Li, Junchao; Pei, Ying; Jiang, Jinyuan
Abstract: Comprehensive assessment of the dissolved organic matter (DOM) released from biochar is essential because it affects the migration and transformation of pollutants. The pyrolysis temperature and feedstock are the main factors affecting the amount and structure of DOM released from biochar. In this study, biochar-derived DOM was produced from three feedstocks at five temperatures (200–600 °C), and the effects of the pyrolysis temperature and feedstock on its components were investigated using UV–vis, Synchronous fluorescence, excitation emission matrix-parallel factor (EEM-PARAFAC) analysis and Fourier transform infrared-two-dimensional-correlation spectroscopy (FTIR-2D-COS). It was found that the biochar-derived DOM contents of the fruit peel and dewatered sludge biochar gradually decreased with increasing pyrolysis temperature; however, the DOM content of fresh human manure biochar increased at 600 °C, and a higher DOM content was obtained at low temperatures. The SUVA254 and SUVA260 shown that most of the aromatic substances in the DOM existed in the hydrophobic fraction. Moreover, the DOM mainly contained humic acid-like substances and protein-like substances. As the pyrolysis temperature increased, the protein-like and humic acid substances exhibited opposite trends, with higher protein-like contents at high temperatures. In addition, based on the FTIR-2D-COS analysis, the variations in the functional groups of the DOM depended on the pyrolysis temperature and the type of feedstock. This study highlights the importance of combining multiple optical techniques to evaluate biochar-derived DOM and provides valuable information for biochar applications. Graphical Abstract: ga1 Highlights: Biochar-derived DOM undergoes secondary reactions at 600 °C. Biochar-derived DOM produced from fresh human manure had high aromaticity at low temperature. Multiple spectral results indicate that the protein-like material became dominant at high temperature. Feedstock and temperature affect the order of functional group variation.